1991
DOI: 10.1007/bf02273881
|View full text |Cite
|
Sign up to set email alerts
|

Dimethylsulfoxide (DMSO) for human single-stage intraoperative tissue expansion and circulatory enhancement

Abstract: Dimethylsulfoxide (DMSO) has been in clinical use since the early 1960s. In 1967 the discovery that DMSO can greatly reduce ischemia in experimental pedicle flaps stimulated its use in plastic surgery by the authors since 1976. In 1987 its ability to soften collagen, thus permitting degrees of immediate intraoperative tissue expansion hitherto unknown, was applied clinically for the first time. Evolving use of topical 70% DMSO alone, in combination with intravenous DMSO, and intravenous DMSO alone with greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…In 1966 ADAMSON et al reported a greatly enhanced flap survival in rat skin flaps subjected to various degrees of ischaemia (8)(9)(10)(11). Further studies using rat models with both DMSO topical and intraperitoneal administration showed reduction of necrosis in skin flaps.…”
Section: Introductionmentioning
confidence: 96%
“…In 1966 ADAMSON et al reported a greatly enhanced flap survival in rat skin flaps subjected to various degrees of ischaemia (8)(9)(10)(11). Further studies using rat models with both DMSO topical and intraperitoneal administration showed reduction of necrosis in skin flaps.…”
Section: Introductionmentioning
confidence: 96%
“…Gastrointestinal adverse reactions were reported in 61 studies. Of these, 10 studies were randomized controlled trials 16, 30, 33, 55, 57, 59, 67, 79, 93, 95 , 49 were cohort studies 2, 4, 7, 9, 18, 19, 23, 2527, 29, 35, 3843, 45, 46, 48, 5054, 58, 60, 66, 68, 69, 71, 73, 83, 8588, 90, 94, 97, 98, 101, 104, 105, 112, 113, 115, 118 , and 2 were case series 84, 109 . Most studies reported the number of patients experiencing an adverse reaction ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…A disadvantage of the tissue expansion technique in large soft tissue defects, which require a long expansion time, is the inherent limit of the ability of the skin and soft tissue to regenerate ( 26 ). To address this concern, many methods have been reported to increase the efficacy of tissue expansion, such as intraoperative acute skin stretching ( 27 ), transplanting bone marrow derived stem cells ( 26 ), and making use of compounds such as botulinum toxin ( 28 ), papaverine ( 29 ), dimethyl sulfoxide ( 30 ), and verapamil ( 31 ). Intermittent intraoperative skin stretching has been shown to improve flap viability by up-regulating VEGF and VEGFR2 at postoperative day 2 and decreasing necrosis by 50-75% at postoperative day 5 ( 27 , 32 ).…”
Section: Discussionmentioning
confidence: 99%